The Relation Between the Blood Pressure with Body Mass Index in the Ages between 18-30 - H Sheikh Sharafi; K Salehi (Iran University of Medical Sciences, 2016)
Abstract Background & Aim: High blood pressure is very important risk factor for cardiovascular disease but more symptoms of this disease are not evident in the adolescent period. This study aimed to investigate the relationship between blood pressure and mean arterial pressure, body mass index, as well as their prevalence at a younger age. Material & Method: This study is a descriptive correlational research. The study population includes Mahabad Azad University students who were selected by non-randomized method. Data were collected by demographic questionnaire, pressure gauge, digital scales and meters. SPSS (v/16) software and Pearson, Spearman and Chi-square test were used for data analysis. Results: In this study, 1050 students between the ages of 18 and 30 years were participated. 32 percent of men and 27% of women have a body mass index between 25 and 30, respectively. 38% of people who had a body mass index between 25 and 30 pre-hypertension stage and five percent of people who had a body mass index greater than 30 degrees had high blood pressure. Chi-square test showed no significant difference between genders in terms of body mass index (p=0.106). Spearman test showed a significant relationship between BMI and blood pressure (p<0.001). Also Pearson test showed a significant correlation between mean arterial pressure and body mass index. Conclusion: The results showed that body mass index among young people and blood pressure in young men is high and this can be a serious warning for the authorities to identify risk factors and applying preventive measures for this age group.